1975
DOI: 10.1159/000468197
|View full text |Cite
|
Sign up to set email alerts
|

Blood Serotonin in Schizophrenie Children

Abstract: Blood serotonin levels were measured in schizophrenic children, all of whom showed manifestations of illness in the first 2 years of life, and controls. Serotonin levels were higher in patients (mean = 0.267 μg/ml) than in controls (mean = 0.218 μg/ml), although the difference did not reach statistical significance. Serotonin levels were significantly higher in patients with florid psychosis and those with lower IQs than in patients in remission or partial remission or higher IQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Investigation have been made from various as pects mainly concerning serotonin metabolism. The blood serotonin level in autistic children has been deter mined by a number of investigators including Schain and Freedman [1961], Hanley et al [1977], Yuwiler et al [1975], Campbell et al [1974Campbell et al [ , 1975, Ritvo et al [1970], Ritvo [ 1977], Boullin et al [ 1970Boullin et al [ , 1971 and Suemitsu et al [1974], All these investigators reported that the blood serotonin level was or tended to be higher in autistic chil dren than in a control group. Our present study likewise showed significantly higher blood serotonin levels in au tistic children than in normal children.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation have been made from various as pects mainly concerning serotonin metabolism. The blood serotonin level in autistic children has been deter mined by a number of investigators including Schain and Freedman [1961], Hanley et al [1977], Yuwiler et al [1975], Campbell et al [1974Campbell et al [ , 1975, Ritvo et al [1970], Ritvo [ 1977], Boullin et al [ 1970Boullin et al [ , 1971 and Suemitsu et al [1974], All these investigators reported that the blood serotonin level was or tended to be higher in autistic chil dren than in a control group. Our present study likewise showed significantly higher blood serotonin levels in au tistic children than in normal children.…”
Section: Discussionmentioning
confidence: 99%
“…They found that there was an inverse relationship between age and serotonin or platelet values in the normal population, that whole blood serotonin concentrations and platelet counts were significantly higher in a group of autistic children than among age-matched controls, and that, in general, serotonin values per platelet did not differ between age-matched groups of autistics and controls, the exception being that very young autistic children had a higher variability of serotonin per platelet values than the corresponding controls. Campbell, Friedman, DeVito, Greenspan, and Collins (1974) and Campbell et al (1975) demonstrated that autistic children tended to have higher platelet-rich plasma serotonin levels than children matched for age, sex, and verbal IQ scores, and that severely retarded autistic children had higher serotonin levels than those who were moderately or mildly retarded. Additionally, psychotic autistic children had higher serotonin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies of amine metabolism have been implicated in some behavioral disorders of childhood. Alterations in serotonin metabolism and blood levels were found in certain retarded, schizophrenic and autistic children (Boullin et al, 1970;Coleman, 1973; P age, 1968\Partington et al, 1973Ritvo et al, 1970;Schain and Freedman, 1961;Campbell et al, 1974Campbell et al, , 1975. Others have found abnormalities in catecholamine metabolism in autistic and atypical children (Cohen et al, 1975).…”
mentioning
confidence: 99%